Fear of Missing Out (FOMO) as a Mediator of Anxiety on Social Media Fatigue in Early Adulthood - Farra Anisa Rahmania; Jihan Salsabila Ramadhayanti; Tassya Aliyah Dwi Andini; Sumedi P. Nugraha (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
Several psychological issues are associated with excessive use of social media, including anxiety, Social Media Fatigue, and Fear of Missing Out (FOMO). Therefore, this research aimed to examine the mediating role of FOMO between anxiety and Social Media Fatigue. The quantitative analysis involved 224 early adulthood individuals as participants, using the Generalized Anxiety Disorder, Social Media Fatigue, and FOMO Scales as instruments. The path analysis result showed that FOMO acted as a mediator between anxiety and Social Media Fatigue. The mediation was partial since anxiety directly influenced Social Media Fatigue with FOMO acting as a mediator. Future research should also be conducted to explore other stronger mediating variables between anxiety and Social Media Fatigue.